THE REASON OF IMPOLITENESS STRATEGY OF 7 YEAR-OLD CHILDREN - Suerni . .; Amrin . Saragih; Rahmad . Husein (Universitas Negeri Medan, 2021)
ABSTRACTThe objectives of this study is to explain the reason of using the Impoliteness Strategy realized by 7- Year- Old Children. Research design This research is descriptive qualitative research. Data analysis To obtain the data 10 children were observed In doing the analysis. Miles, Huberman and Saldana 2014 steps theories were used. To achieve the objective the steps used were data condensation, data display, and data verification. Result. The result shows that the reason of using the impoliteness strategy were mocking (30%), to get / to show power over action or conversation (30%), to vent negative feeling (28%), to show disagreement (12%), while to entertain the target audience wasn't found (0%).Keywords: Reason, Impoliteness, Mocking, Entertain